Interaction between the economic growth and the construction industry: A time series analysis on Turkey (2000-2012) - Bilal Kargi (Emerging Markets Journal, 2013)
In this study the relation between the economic growth and the construction industry has been tackled. While the growth the rate of the construction industry in the developing countries is more than the GDP growth rate, it is detected that the percent age it takes in the GDP of developed countries relatively diminishes. On the other hand the construction industry's growth in the economic fluctuation periods, in the aftermath of a recession, is more than the GDP. These two proposals are tested by the quarterly data of 2000:01-2012:03 for Turkey. Additionally the relation between the economic growth and the construction industry is subjected to the Granger causality test.
Keywords: O40; 330; Economic Growth; Construction Industry; Time Series Analysis